A smart fishing suite - Mallalieu, Kim I.; Lessey, Mark (Technical Centre for Agricultural and Rural Cooperation, 2012)
A range of cell phone applications, known as mFisheries, improves market connections, supply chain efficiency and safety at sea for small-scale fishers in Trinidad and Tobago.